Analysis of resonant characteristics of Yunnan power grid under different operating modes of AC/DC hybrid systems. Issue 16 (15th January 2019) - Helin, Liu; Jun, Wen; Shiyou, Yu; Jiaqi, Li
Abstract : Resonance or harmonic amplification occurs when the frequency of the harmonics generated by the converter station is near the inherent resonance frequency of the substation. Considering there are six DC projects in the Yunnan power grid, analysing the resonant characteristics of the grid is imperative for safety reasons. This study establishes a simulation platform of the Yunnan power grid based on the Power System Analysis Software Package and formulates the modelling principles and simulation steps. In order to successfully analyse the resonant characteristics of a substation under normal operation mode and put forward any necessary suggestions, the impedance frequency of all 500 kV substations in the power grid are scanned. This is followed by studying, the influence of different operation modes of Yunnan power grid and different operation modes of DC system of Luxi converter station on the resonant characteristics of Yunnan substation. Based on these results, effective measures for resonance suppression are proposed.